Concepts and considerations for enhancing RNAi efficiency in phytopathogenic fungi for RNAi-based crop protection using nanocarrier-mediated dsRNA delivery systems - Ray, Poonam; Sahu, Debashish; Aminedi, Raghavendra; Chandran, Divya (Frontiers in Fungal Biology, 2022)
Existing, emerging, and reemerging strains of phytopathogenic fungi pose a significant threat to agricultural productivity globally. This risk is further exacerbated by the lack of resistance source(s) in plants or a breakdown of resistance by pathogens through co-evolution. In recent years, attenuation of essential pathogen gene(s) via double-stranded (ds) RNA-mediated RNA interference (RNAi) in host plants, a phenomenon known as host-induced gene silencing, has gained significant attention as a way to combat pathogen attack. Yet, due to biosafety concerns regarding transgenics, country-specific GMO legislation has limited the practical application of desirable attributes in plants. The topical application of dsRNA/siRNA targeting essential fungal gene(s) through spray-induced gene silencing (SIGS) on host plants has opened up a transgene-free avenue for crop protection. However, several factors influence the outcome of RNAi, including but not limited to RNAi mechanism in plant/fungi, dsRNA/siRNA uptake efficiency, dsRNA/siRNA design parameters, dsRNA stability and delivery strategy, off-target effects, etc. This review emphasizes the significance of these factors and suggests appropriate measures to consider while designing in silico and in vitro experiments for successful RNAi in open-field conditions. We also highlight prospective nanoparticles as smart delivery vehicles for deploying RNAi molecules in plant systems for long-term crop protection and ecosystem compatibility. Lastly, we provide specific directions for future investigations that focus on blending nanotechnology and RNAi-based fungal control for practical applications.